Proteomic Analysis of Embryo Isolated From Mature Jatropha curcas L. Seeds - Ramzan, Ayesha; Shah, Mohibullah; Ullah, Najeeb; Sheheryar,; Nascimento, José R. S.; Campos, Francisco A. P.; Domont, Gilberto B.; Nogueira, Fábio C. S.; Abdellattif, Magda H. (Frontiers in Plant Science, 2022)
Jatropha curcas L. is a non-edible oilseed containing almost 40% of seed oil and is famous as the best source of raw material for biofuel production. J. curcas seeds contain three main tissues including inner integument, endosperm, and embryo. To best understand the physiological events related to specific tissues, it is important to perform the proteome analysis of these tissues. Previously we have explored the pattern of reserves deposition and tissue-specific biological pathways by analyzing the proteome of the inner integument and endosperm and organelles like plastids and gerontoplasts isolated from these tissues. The focus of the present study was to perform proteomic analysis of the embryo isolated from the mature seeds of J. curcas. This analysis resulted in the identification of 564 proteins of which 206 are not identified previously from any other tissue of this plant. The identified proteins were functionally classified using the MapMan classification system revealing various proteins involved in different functionalities. The proteins involved in transport functions and those with proteolytic activity were determined through TCDB and MEROPS databases, respectively. In addition to identifying a large number of proteins participating in various metabolic processes, we found several proteins involved in defense functions, such as members of chaperones and the ubiquitin-proteasome system. Similarly, members of the legumin and vicilin family of seed storage proteins were also identified which in addition to their storage function, are involved in defense. We have also reported here proteases belonging to different mechanistic classes and involved in diverse physiological functions. Last but not the least, several classes of transport-related proteins were also identified which are discussed concerning their function in the transportation of different nutrients across the embryo. To the best of our knowledge, this study reported the highest number of proteins identified from the embryo of mature J. curcas seeds, most of which are essential for seed germination, reflecting the fact that many proteins required for germination are already present in the mature embryo.